2009
DOI: 10.1590/s0006-87052009000200022
|View full text |Cite
|
Sign up to set email alerts
|

Fontes, doses e modo de aplicação de nitrogênio em feijoeiro no sistema plantio direto

Abstract: O manejo do N correspondente à maior produtividade de grãos, do ponto de vista econômico, muitas vezes não é o mais rentável e, portanto, não será adequado para recomendação ao produtor. O objetivo do trabalho foi o de estudar o efeito de fontes, doses e parcelamento do nitrogênio no desenvolvimento e na produtividade de grãos do feijoeiro de inverno no sistema plantio direto, correlacionado com análise econômica simples, em Latossolo Vermelho Distrófico argiloso, em Selvíria (MS), em 2005. O delineamento expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
3
11
0
15
Order By: Relevance
“…These results are similar to multiple studies that have demonstrated the positive effect of N on 100 grain weight (Rapassi et al, 2003;Silva et al, 2004;Alvarez et al, 2005;Teixeira et al, 2005;Binotti et al, 2009). However, Bassan et al (2001) observed higher values in the inoculated treatments in relation to the non-inoculated ones and attributed the result to the non-existence of efficient native strains.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results are similar to multiple studies that have demonstrated the positive effect of N on 100 grain weight (Rapassi et al, 2003;Silva et al, 2004;Alvarez et al, 2005;Teixeira et al, 2005;Binotti et al, 2009). However, Bassan et al (2001) observed higher values in the inoculated treatments in relation to the non-inoculated ones and attributed the result to the non-existence of efficient native strains.…”
Section: Resultssupporting
confidence: 92%
“…However, an increase in net returns, which should be the ultimate goal of rural producers, is not always linked to technology or a process that enables an increase in yield, as noted by Binotti et al (2009). These authors found that application rates of ammonium sulfate that led to the highest bean yields did not result in higher values in net return, due to the high costs of N fertilizers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This corroborates Binotti et al (2007), where a 62% higher productivity was obtained with the use of N, with increase in the total N in leaves and grains found an increase in productivity of about 100 kg ha -1 when the application of N was released in different moments. In turn, Binotti et al (2009) found no difference in productivity between provision of N in a single moment, at sowing, or dividing fertilization in different moments, and still, nitrogen content in the leaf was higher when dividing fertilization.…”
Section: Introductionmentioning
confidence: 70%
“…Estes resultados corroboram os de Cardoso (2011) que não obteve diferença significativa no número de vagens por planta, no nú-mero de grãos por vagem e na massa de 100 grãos, em razão da aplicação de ureia, SA, nitrato de cálcio, NA e Ajifer, em cobertura, no feijoeiro. Binotti et al (2009) e Arf et al (2011 também não observaram efeito significativo de fontes nitrogenadas no número de grãos por vagem, provavelmente, conforme Andrade et al (1998), porque esta é uma caracterís-tica varietal, pouco influenciada pelo ambiente.…”
Section: Tratamentosunclassified